Re-evaluating the LD50 requirements in the codified potency testing of veterinary vaccines containing Leptospira (L.) serogroup Icterohaemorrhagiae and L. serogroup Canicola in the United States. (November 2018) - Walker, Angela; Olsen, Renee; Toth, Mindy; Srinivas, Geetha
Abstract: Approximately one-third of the reportable USDA Category D and E laboratory animals in the United States are expended on the potency testing of leptospiral vaccines by the codified hamster vaccination-challenge assay. Valid tests require ≥80% of challenge controls to succumb to disease and an LD50 between 10 and 10, 000. This work evaluates the risk associated with the removal of LD50 limits; thereby, eliminating back-titration hamsters from in vivo potency assays for Leptospira (L.) serogroups Canicola and Icterohaemorrhagiae. The impact was assessed through 1) retrospective analysis of industry and CVB serial release data from July 2011–April 2015 and 2) evaluation through vaccination-challenge assays. For the initial vaccination-challenge assays (n = 3/serogroup), one group received potent bacterin (PB) and six groups received subpotent bacterins (SB1-SB6). PB and SB1 were challenged with a single dilution of Leptospira between 10 and 10, 000 LD50. SB2-SB6 received serial dilutions of more concentrated challenge. Based on the retrospective analysis and in vivo assays, 80% of the challenge controls succumbing to disease reasonably ensured the minimal LD50 was administered. Subpotent vaccines were not at increased risk for being deemed potent when challenged with >10, 000 LD50, but potent vaccines were at risk of being deemed subpotent when challenged with >10, 000 LD50. Highlights: 80% mortality in challenged controls and an LD50 of 10-10, 000 is codified. Eliminating back-titration hamsters could reduce animal use by 50% per test. 80% mortality in challenge controls alone prevents insufficient challenge dose. Subpotent serials are not at increased release risk with >10, 000 LD50 of challenge. Marginally potent serials may appear subpotent when challenged with >10, 000 LD50.